The fashion disaster that changed my life - Myracle, Lauren 1969- (Dutton Children's Books, 2005)
Seventh-grader Alli inadvertently arrives on the first day of school with underwear static-clinging partly outside her pant leg.
Keywords: First day of school -- Fiction; Schools -- Fiction; Friendship -- Fiction; Family life -- Fiction; Jugendbuch